Malignant peripheral nerve sheath tumor of the shoulder: A rare case highlighting the role of multimodal management - Oukassem Siham; Abourak Chaimae; Sqalli Houssaini Abdelkader; Guennouni Asma; Moatassim Billah Nabil; Ittimad Nassar; Imrani Kaoutar; Iraqui Iman; Derqaoui Sabrine; Znati Kaoutar (Radiology Case Reports)
Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive sarcomas often associated with neurofibromatosis type 1 (NF1) or prior radiation therapy. We report the case of a 26-year-old male who presented with a rapidly enlarging, painful mass in the left shoulder initially misdiagnosed as an abscess. MRI revealed a large extra-compartmental lesion with heterogeneous enhancement infiltrating the trapezius muscle. Histopathology confirmed MPNST, showing high mitotic activity (16/10 HPF), 10% necrosis, and a Ki-67 index of 40%, with diffuse Sox10 and focal S100 positivity. The patient received neoadjuvant radiotherapy followed by complete surgical excision and defect reconstruction using a pedicled trapezius flap and a split-thickness skin graft. This case highlights the importance of early imaging, multidisciplinary planning, and multimodal treatment in the management of MPNSTs.